ASSESSMENT OF THE GROUNDWATER RECHARGE POTENTIAL AREAS USING GIS IN KAJOR KULON HAMLET, SELOPAMIORO, IMOGIRI, BANTUL, YOGYAKARTA - Saputra, Deni Rahman; Yudono, Andi Renata Ade; Partoyo, Partoyo (UI Scholars Hub, 2020)
Groundwater balance occurs in the presence of recharge and discharge. The process of entering the water in soil takes place with an infiltration-percolation to aquifers. The groundwater recharge area is identified by lithology, land use, slope, rainfall, land, and landform. Kajor Kulon Hamlet, Selopamioro Village, Imogiri Sub-district, Bantul Regency, Special Region of Yogyakarta becomes an area with hilly morphology, active fault areas, and including drought-prone regions. Change of the land function in hilly areas by making settlements and un-irrigation field for farming may cause decreased ability as a recharge area. Research aim sare to assessing, determining, and analyzing the conditions of the establishment in the research area. The variables used include land use, the slope of the land, rainfall, and soil texture as thematic maps to analysis its land ability. Data collection methods are measurement, inquiry, and mapping. Furthermore, the method of analysis is based on the Geographic Information Systems (GIS) with scoring-weighted overlay method. The results showed the classification of the between low, medium, and high. The medium class is currently occupying 67% of the area in the research area with an area of 719,916.03 m2 . The distribution of each class is expressed through the groundwater recharge area map. The GIS is very efficient and effective in facilitating groundwater recharge area analysis